A corpus linguistic investigation into the media representation of the suffrage movement - Gupta, Katherine E. (2013)
This thesis focuses on the representation of the women's suffrage movement in The Times newspaper between 1908 and 1914. I assemble two focused corpora from texts from News International's The Times Digital Archive: the 7 million word Suffrage corpus and the 400,000 word Letters to the Editor corpus. I then combine historical research into the suffrage movement, corpus linguistic analysis of social discourses and approaches drawn from critical discourse analysis. The suffrage movement was not a unified one; it was composed of various groups with differing backgrounds, ideologies and aims. Historians working with suffragist-produced texts have noted different terminology used to describe different factions of the movement. Less attention has been paid to how the suffrage movement was perceived by those outside the movement, and particularly how it was represented in the press. Central to this thesis is Deleuze and Guattari's (1987) argument that polyvocal, heterogeneous entities are simplified and erased by those in power. I demonstrate that such a simplification of diverse suffrage identities occurs on a lexical level through the consistent use of suffragist to describe all suffrage campaigners, including acts more commonly associated with suffragettes. This conflation of identities also occurred on a textual level through what I define as the 'suggestive placement' of texts within an article. I argue that suggestively placed prosuffrage texts offering a counter discourse are read in the context of the master narrative of suffrage campaigners as violent and dangerous. By focusing on a self-contained, historical movement this thesis is able to analyse changes in historical political discourses, offers corpus linguistic researchers working with contemporary social movements a point of comparison and proposes a methodology for working within the constraints of the data to get useful results. As an interdisciplinary project, it will offer historians a different perspective on ideologies as expressed through language.